Production of steers fed African oil palm (Elaeis guineensis L.) fiber with the addition of organic minerals, grazing African star - Gómez-Vázquez, Armando; Govea-Luciano, Alejandra; De la Cruz, Lázaro; Cruz Hernández, Aldenamar; Álvarez González, Carlos; Brito Manzano, Nancy; Bautista Galvez, Arely; Chay Canul, Alfonso; León Nájera, José (Cuban Journal of Agricultural Science, 2018)
The effect of the addition of an organic mineral (Bioplex Quality Meat), on the gain and digestibility of fattening steers in grazing and a complement of African oil palm fiber as complementary forage, under tropical conditions was studied. Forty cross steers (Bos taurus x Bos indicus) were used, with average initial live weight of 276 ± 28 kg, for 120 days. They were fed individually with 1 kg d-1 of concentrate (14% CP) and African oil palm fiber (AOPF), in a completely randomized design, according to the following treatments: 1)Control, only grazing (CG); 2) CG+ African oil palm fiber (AOPF-0); 3) CG + AOPF + 15 g animal-1 d-1 of Bioplex Quality Meat (AOPF-15) and 4) CG + AOPF + 30 g animal-1 d-1 Bioplex Quality Meat (AOPF-30). The daily weight gain of the steers was improved with Bioplex Quality Meat showing a linear effect (P <0.01); (CG = 492, AOPF-0 = 554, AOPF-15 = 637, AOPF-30 = 792 g d-1 Bioplex Quality Meat), which was associated with an increase in the intake (linear effect P <0.05) of African oil palm fiber (CG = 0.0, AOPF-0 = 3.06, AOPF-15 = 3.08, AOPF-30 = 3.36 kg d-1) and higher DM digestibility (P <0.05), compared to the control group (CG = 67.13, AOPF-0 = 74.26, AOPF-15 = 72.29, AOPF-30 = 72.46%). There were no effect on total forage or DM intake was detected.The results allow concluding that Bioplex Quality Meat increases the nutrient availability of African oil palm fiber, which improves daily weight gain.Key words: organic minerals, African oil palm, steers, digestibility.